Classification of Theories about the Origin of Religions - Alvargonzález, David (Journal for the Academic Study of Religion, 2021)
In this article, I will classify theories about the origin of religions, distinguishing two groups of theories: those upholding the revealed origin of religion and those denying it. The former can be split into two: theories assuming that revelation is an encounter between humans and certain finite extraterrestrial intelligences (an encounter taking place in the past or being expected for the future) and those defining revelation as the presence before humans of either a transcendent, immaterial God or certain mythological or historical beings sent by him. As for the latter, two varieties exist as well: theories holding that non-human animals also have religion, and those restricting religion to humans and explaining their origin through the relationships of human groups with their environment. To classify the latter, I will make use of Gustavo Bueno’s theory of anthropological space. Finally, I will touch on the necessarily partisan components of my classification.